The association between biliary tract inflammation and risk of digestive system cancers: A population-based cohort study. Issue 31 (August 2016) - Tsai, Tsung-Yu; Lin, Che-Chen; Peng, Cheng-Yuan; Huang, Wen-Hsin; Su, Wen-Pang; Lai, Shih-Wei; Chen, Hsuan-Ju; Lai, Hsueh-Chou
Abstract : Abstract: The relationship between biliary tract inflammation (BTI) and digestive system cancers is unclear. This study aimed to evaluate the association between BTI and the risks of digestive system cancers. Using the Taiwan National Health Insurance claims data, information on a cohort of patients diagnosed with BTI (n = 4398) between 2000 and 2009 was collected. A comparison cohort of sex-, age-, and index year-matched persons without BTI (n = 17, 592) was selected from the same database. The disease was defined by the ICD-9-CM. Both cohorts were followed until the end of 2010 and incidences of digestive system cancers were calculated. The results revealed an increase in adjusted hazard ratio (aHR) of biliary tract cancer (24.45; 95% confidence interval [CI]: 9.20–65.02), primary liver cancer (1.53; 95% CI: 1.07–2.18), and pancreatic cancer (3.10; 95% CI: 1.20–8.03) in patients with both gallbladder and BTI. The aHR of stomach cancer was also found to be increased (2.73; 95% CI: 1.28–5.81) in patients with gallbladder inflammation only. There were no differences in esophageal cancer (aHR: 0.82; 95% CI: 0.23–2.87) and colorectal cancer (aHR: 0.92; 95% CI: 0.59–1.45). The aHR for digestive system cancers increased by 3.66 times (95% CI: 2.50–5.35) and 12.20 times (95% CI: 8.66–17.17) in BTI visits frequency averaged 2 to 4 visits per year and frequency averaged ≥5 visits per year, respectively. Patients with BTI have significantly higher risk of digestive system cancers, particularly biliary tract, pancreatic, and primary liver cancers, compared with those who are without it.